Optimizing the Use of Electronic Navigation Devices when Sailing at Night on MV. Hijau Segar - Umasangadji, Fahmi; Saleh, Sahar; Palapa, Arika; Nurmala, Eka; Murtalis, Murtalis (PT. Alpha Trianguli Australis, 2025)
The shipping world is one of the means of sea transportation engaged in the shipping sector. When we sail at night, it takes skill in using electronic navigation devices, the use of electronic navigation devices is not only in poor conditions and when visibility is limited to cause a risk of collision when the ship is sailing at night but also helps officers on board in determining the course, position, distance of the ship with objects around the ship. This study uses a qualitative explanatory approach to understand the phenomena that enter through non-numerical data analysis. The results of this study are: 1) Procedures for using electronic navigation devices on KM. Hijau Segar include preparation of navigation devices, operation of devices, monitoring during sailing, handling disturbances, closing and storage; and 2) Obstacles and solutions to prevent disturbances in navigation devices on KM. Hijau Segar include technical obstacles, environmental disturbances, signal disturbances, limited human resources, power outages.